Toxicity study of ethanolic stem bark extract of Xylopia aethiopica on fertility indices of male rats: An experimental study - Ben Enoluomen Ehigiator; Elias Adikwu (Shahid Sadoughi University of Medical Sciences, 2020)
Background: The uses of toxicologically unscreened plants to enhance fertility can be associated with adverse consequences. Objective: This study aimed to evaluate the effect of the ethanolic stem back extract of X. aethiopica (EEXA) on the fertility indices of male albino rats. Materials and Methods: Sixty male albino rats (weighing 200-250 gr) were grouped and administered by gavage with 200-800 mg/kg of EEXA daily for 15, 30, and 60 days. After the administration of EEXA, the rats were weighed and sacrificed. Blood samples were collected, serum samples were extracted, and evaluated for testosterone, follicle stimulating hormone, prolactin, estradiol, luteinizing hormone and progesterone levels. The testes, epididymis, and prostrate were harvested, weighed and testes were evaluated for sperm parameters. Results: Significant increase in body weight (p = 0.02) with significant decreases in testes (p = 0.01), epididymis (p = 0.01), and prostate (p = 0.02) weights occurred in rats administered with EEXA when compared to the control group. Significant (p < 0.001) dose and time- dependent decreases in sperm count, volume, motility, and normal morphology were obtained in rats administered with EEXA when compared to the control group. However, there were no significant (p > 0.05) effects on sperm pH when compared to control. Furthermore, luteinizing hormone, follicle stimulating hormone, and testosterone levels were significantly decreased whereas serum prolactin, estradiol, and progesterone levels were significantly increased in a dose-dependent fashion in rats administered with EEXA when compared to the control group. Conclusion: The findings in this study showed that the use of X. aethiopica may be detrimental to male reproduction function.